2021
DOI: 10.1051/0004-6361/202040030
|View full text |Cite
|
Sign up to set email alerts
|

Day-night differences in Mars methane suggest nighttime containment at Gale crater

Abstract: We report new measurements of atmospheric methane by the Curiosity rover’s Tunable Laser Spectrometer that is part of the Sample Analysis at Mars suite (TLS-SAM), finding nondetections during two daytime measurements of average value 0.05 ± 0.22 ppbv (95% confidence interval CI). These are in marked contrast with nighttime background levels of 0.52 ± 0.10 (95% CI) from four measurements taken during the same season of northern summer. This large day-night difference suggests that methane accumulates while cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
(48 reference statements)
1
33
0
Order By: Relevance
“…Analyses of atmospheric samples and water released from clay minerals indicate the preferential loss of light isotopes, consistent with atmospheric escape (Webster et al 2013;Mahaffy et al 2015). Atmospheric methane is found to vary diurnally and seasonally, indicating active production, likely from subsurface seepage (Webster et al 2021). Meteorological observations over multiple Mars years have revealed the influence of the crater on wind, pressure, and atmospheric dust (Rafkin et al 2016).…”
Section: Marsmentioning
confidence: 67%
“…Analyses of atmospheric samples and water released from clay minerals indicate the preferential loss of light isotopes, consistent with atmospheric escape (Webster et al 2013;Mahaffy et al 2015). Atmospheric methane is found to vary diurnally and seasonally, indicating active production, likely from subsurface seepage (Webster et al 2021). Meteorological observations over multiple Mars years have revealed the influence of the crater on wind, pressure, and atmospheric dust (Rafkin et al 2016).…”
Section: Marsmentioning
confidence: 67%
“…There are reports of both positive and non-detections of methane on Mars by, respectively, observations by the MEx and ExoMars space probes [25,26]. The discrepancy between these has generated much debate [27][28][29][30][31][32].…”
Section: Marsmentioning
confidence: 99%
“…Regarding the near-surface abundance levels detected by MSL, each emission source should satisfy sustainable midnight values of ∼0.4 ppbv (Webster et al, 2018). Recently, Webster et al (2021) reported the first enrichment observations performed during the daytime. Two daytime measurements close to midday of average value 0.05 ppbv ±0.22 ppbv (95% confidence interval) were reported between the southern winter solstice and the equinox (L s = 121° and 134°).…”
Section: Evaluation Of the Emission Source Responsible For The Methane Detected By Mslmentioning
confidence: 99%
“…In this way, the nighttime abundance of methane from a surface source, restricted from vertical mixing by the stable nighttime PBL, could be much higher than in the well-mixed daytime. Recent enrichment observations suggest that the values during daytime are below the detection limit of TGO (Webster et al, 2021). Viúdez-Moreiras, Arvidson, et al (2020) suggested that the methane abundance detected by MSL could be significantly influenced by local meteorology and/or that methane source emissions could be highly dependent on location, areocentric solar longitude (L s ), and local time.…”
mentioning
confidence: 99%